Diagnosis and treatment of incomplete Kawasaki disease - Santoso, Stephanie Aurelia; Wangunhardjo, Gani; Santoso , Irene Aurelia (Indian Journal of Case Reports, 2025)
Kawasaki disease (KD) is a self-limiting systemic vascular condition predominantly affecting children under five, characterized by prolonged fever and specific clinical signs. Diagnosis is made through the presence of a fever lasting over 5 days and at least four of five criteria, which include oral mucosa changes, extremity alterations, rash, and absence of purulent conjunctivitis or lymphadenopathy. The disease presents significant risks, including coronary artery aneurysms, making timely diagnosis and treatment critical. This case report details a 3-year-old boy with incomplete KD, who manifested with fever, abdominal pain, and rash. Laboratory tests showed leucocytosis and elevated inflammatory markers, leading to an echocardiographic diagnosis of coronary artery dilation. Treatment with high-dose intravenous immunoglobulin and aspirin resulted in symptomatic improvement and stabilization of coronary artery dimension. KD remains the leading cause of acquired heart disease in children, underscoring the importance of recognizing its signs and initiating early treatment to prevent long-term complications.